Berbamine, a novel nuclear factor κB inhibitor, inhibits growth and induces apoptosis in human myeloma cells - Liang Yun; Xu Rong-zhen; Zhang Lei; Zhao Xiao-ying (Acta Pharmacologica Sinica, 2016)
Aim: We sought to investigate the effect of berbamine on the growth of human multiple myeloma cell line KM3 and elucidate the mechanism of its action. Methods: MTT assay was used to determine the inhibitory effect of berbamine alone or combined with chemotherapeutic drugs. Flow cytometry was performed to characterize cell cycle profile in response to berbamine treatment. Western blot was used to measure the protein levels of p65, IκB Kinase α (IKKα), TNFAIP3 (A20), IκBα, p-IκBα, cyclinD1, Bcl-2, BAX, Bcl-xL, Bid, and survivin. Results: Berbamine inhibits the proliferation of KM3 cells in a dose- and time-dependent manner. Combination of berbamine with dexamethasone (Dex), doxorubicin (Dox) or arsenic trioxide (ATO) resulted in enhanced inhibition of cell growth. Flow cytometric analysis revealed that KM3 cells were arrested at G1 phase and apoptotic cells increased from 0.54% to 51.83% for 36 h. Morphological changes of cells undergoing apoptosis were observed under light microscope. Berbamine treatment led to increased expression of A20, down-regulation of IKKα, p-IκBα, and followed by inhibition of p65 nuclear localization. As a result, NF-κB downstream targets such as cyclinD1, Bcl-xL, Bid and survivin were down-regulated. Conclusion: Berbamine inhibits the growth of KM3 cells by inducing G1 arrest as well as apoptosis. Berbamine blocks NF-κB signaling pathway through up-regulating A20, down-regulating IKKα, p-IκBα, and then inhibiting p65 nuclear translocation, and resulting in decreased expression of the downstream targets of NF-κB. Our results suggest that berbamine is a novel inhibitor of NF-κB activity with remarkable anti-myeloma efficacy.